2022
DOI: 10.3390/diagnostics12010126
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning Segmentation of Epicardial Adipose Tissue Using Four-Chamber Cardiac Magnetic Resonance Imaging

Abstract: In magnetic resonance imaging (MRI), epicardial adipose tissue (EAT) overload remains often overlooked due to tedious manual contouring in images. Automated four-chamber EAT area quantification was proposed, leveraging deep-learning segmentation using multi-frame fully convolutional networks (FCN). The investigation involved 100 subjects—comprising healthy, obese, and diabetic patients—who underwent 3T cardiac cine MRI, optimized U-Net and FCN (noted FCNB) were trained on three consecutive cine frames for segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The free‐running ME‐GRE framework enabled quantitative fat measurements across the cardiac cycle, which allows to select a preferred frame for various adipose tissue characterization, 67 and in the current volunteer study, a variable FF pattern was consistently observed as a function of time, indicating an heterogeneity of the pericardial fatty tissue. This result suggests that motion‐averaged or frozen‐motion (i.e., triggered) visualizations might only allow for partial or incomplete tissue characterization, a finding that can be linked to similar reports on the effect of respiratory motion on R 2 * quantification in the liver 68,69 .…”
Section: Discussionmentioning
confidence: 64%
“…The free‐running ME‐GRE framework enabled quantitative fat measurements across the cardiac cycle, which allows to select a preferred frame for various adipose tissue characterization, 67 and in the current volunteer study, a variable FF pattern was consistently observed as a function of time, indicating an heterogeneity of the pericardial fatty tissue. This result suggests that motion‐averaged or frozen‐motion (i.e., triggered) visualizations might only allow for partial or incomplete tissue characterization, a finding that can be linked to similar reports on the effect of respiratory motion on R 2 * quantification in the liver 68,69 .…”
Section: Discussionmentioning
confidence: 64%
“…Two studies presented novel MRI techniques to assess EAT quantification. Daudé et al 53 employed fully convolutional networks that were used for cardiac volume segmentation techniques to measure the EAT area on horizontal long-axis four-chamber cine MRI multi-frame images. This approach was developed to overcome interobserver variability and shorten the time-consuming nature of manual analysis.…”
Section: Methodological Studiesmentioning
confidence: 99%
“…This approach was developed to overcome interobserver variability and shorten the time-consuming nature of manual analysis. 53 …”
Section: Methodological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Transthoracic echocardiography is the main tool used to quantify and measure the thickness and the volume of epicardial fat [ 39 ]. Computer tomography (CT) and magnetic resonance imaging (MRI) are mainly used to evaluate the volume of EAT because of their high spatial resolution [ 40 ].…”
Section: Physiology and Pathophysiologymentioning
confidence: 99%